Implementing Circular Economy Techniques for the Optimal Management of Recyclable Solid Waste Using the M-GRCT Decision Support Model - Camilo-A. Vargas-Terranova; Javier Rodrigo-Ilarri; María-Elena Rodrigo-Clavero; Alejandro Parra-Saad (Applied Sciences, 2022)
This article analyzes the implementation of a circular economy model for the management of reusable solid waste in the Colombian municipalities of Arbeláez (province of Cundinamarca) and Tibasosa (province of Boyacá). The analysis is conducted using M-GRCT, a circular economy decision support model for the design of recyclable waste management systems in low-income municipalities. The model allows for performing calculations on a set of two scenarios integrating a sociocultural dynamics assessment—this being a characteristic feature of this type of municipalities. Results show that both the linear and circular models of waste management are economically viable. However, the particular conditions of each municipality, the tariff system, the number of subscribers and the variations in costs and inflation in each municipality affect the results of economic viability. In addition, the waste production scale and the volumes of recoverable waste also affect the results. All these factors are reflected in the scenarios analyzed. In terms of economic viability, the circular model presents better results in Arbeláez, while in the municipality of Tibasosa, the best results are obtained with a linear economy approach.